C^p-parametrization in O-minimal Structures. Issue 1 (9th January 2019) - Kocel-Cynk, Beata; Pawłucki, Wiesław; Valette, Anna
Abstract: We give a geometric and elementary proof of the uniform C^p -parametrization theorem of Yomdin and Gromov in arbitrary o-minimal structures.